Screening of Hemoglobin A1c in Gestational Diabetes among women attending metabolic clinic at a tertiary care hospital in Uttar Pradesh - Sinha, Vivek; Kachhawa, Poonam (Asian Journal of Medical Sciences, 2019)
Background: Gestational diabetes mellitus (GDM) is a common medical condition that complicates pregnancies..Gestational diabetes mellitus (GDM) is a diabetic metabolic disorder that occurs in 4% of all pregnant women and 14% of ethnic groups with more prevalence of type II diabetes. It can be defined as increased or abnormal insulin resistance, decreased insulin sensitivity or glucose intolerance with first diagnosis during pregnancy. Aims and Objectives: The purpose of this study was to evaluate the diagnostic screening value of the HbA1c, prevalence of GDM and associated risk factors. Materials and Methods: The study was conducted at the metabolic clinic; in the department of Biochemistry located at SIMS, Hapur. A semi-structured pretested questionnaire was used for data collection. Following the DIPSI guidelines, patients with plasma glucose values >140 mg/dl were labeled as GDM. Statistical methods used were OR (CI95%), percentage, Chi square. Results: Out of 500, 6.72% had GDM. Among all GDM patients, 64.71% had age more than 30 years, 70.59% had BMI more than 25, 41.18% had gravida more than 3 and p- value was significant with regard to age and BMI. P value was found to be significant for risk factors namely positive family history of Diabetes Mellitus, history of big baby and presence of more than one risk factor. Conclusion: GDM is associated with high BMI, early pregnancy loss, family history of DM and previous history of big baby and there could be more than one risk factor. Thus universal screening followed by close monitoring of the pregnant women for early detection of GDM may help improving maternal and fetal outcomes.